The Influence of Current Ratio, Debt to Asset Ratio and Operating Profit Margin on Return on Assets Empirical Study of Financial Performance at Mitra Niaga Mandiri Cooperative - Anugrah Cahya Putra; Galih Tri Ramdan; Benny Dhevyanto; Krisdiana (PT FORMOSA CENDEKIA GLOBAL, 2025)
Financial performance analysis requires indicators such as the Current Ratio (CR), Debt to Asset Ratio (DAR), and Operating Profit Margin (OPM), which are important tools for companies, including cooperatives. The CR measures a cooperative’s ability to meet its short-term obligations using its current assets. The purpose of this study is to analyze the influence of the Current Ratio (CR), Debt to Asset Ratio (DAR), and Operating Profit Margin (OPM) on Return on Assets (ROA) at Koperasi Mitra Niaga Mandiri Indonesia during the 2019–2024 period. The method used is multiple linear regression with a quantitative approach to evaluate the relationship of these variables both partially and simultaneously on the financial performance of the cooperative. The research data is based on the annual financial reports of 25 cooperative branches that have been operating since 2019. The results of the study indicate that the Current Ratio (CR) and Operating Profit Margin (OPM) have a significant influence on ROA, while the Debt to Asset Ratio (DAR) shows a varying impact depending on the funding structure of each branch. This study contributes theoretically to the cooperative finance literature and provides practical recommendations for cooperative management in optimizing financial resources to improve profitability and operational stability.